Riboflavin as a promising antimicrobial agent? A multi-perspective review - Farah, Nuratiqah; Chin, Voon Kin; Chong, Pei Pei; Lim, Wai Feng; Lim, Chee Woei; Basir, Rusliza; Chang, Sui Kiat; Lee, Tze Yan (Current research in microbial sciences, 2022)
•Riboflavin demonstrates antioxidant and photosensitizing properties.•Riboflavin is able to induce ROS and modulate immune response.•Riboflavin possesses potent antimicrobial activity when used alone or combined with other anti-infectives.•The riboflavin biosynthesis pathway serves as an ideal drug target against microbes.•UVA combination with riboflavin exhibits remarkable antimicrobial effects. Riboflavin, or more commonly known as vitamin B2, forms part of the component of vitamin B complex. Riboflavin consisting of two important cofactors, flavin mononucleotide (FMN) and flavin adenine dinucleotide (FAD), which are involved in multiple oxidative-reduction processes and energy metabolism. Besides maintaining human health, different sources reported that riboflavin can inhibit or inactivate the growth of different pathogens including bacteria, viruses, fungi and parasites, highlighting the possible role of riboflavin as an antimicrobial agent. Moreover, riboflavin and flavins could produce reactive oxygen species (ROS) when exposed to light, inducing oxidative damage in cells and tissues, and thus are excellent natural photosensitizers. Several studies have illustrated the therapeutic efficacy of photoactivated riboflavin against nosocomial infections and multidrug resistant bacterial infections as well as microbial associated biofilm infections, revealing the potential role of riboflavin as a promising antimicrobial candidate, which could serve as one of the alternatives in fighting the global crisis of the emergence of antimicrobial resistance seen in different pathogenic microbes. Riboflavin could also be involved in modulating host immune responses, which might increase the pathogen clearance from host cells and increase host defense against microbial infections. Thus, the dual effects of riboflavin on both pathogens and host immunity, reflected by its potent bactericidal effect and alleviation of inflammation in host cells further imply that riboflavin could be a potential candidate for therapeutic intervention in resolving microbial infections. Hence, this review aimed to provide some insights on the promising role of riboflavin as an antimicrobial candidate and also a host immune-modulator from a multi-perspective view as well as to discuss the application and challenges on using riboflavin in photodynamic therapy against various pathogens and microbial biofilm-associated infections. [Display omitted]